2008
DOI: 10.1074/jbc.m802513200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Cathepsins Trigger Caspase-dependent Cell Death through Cleavage of Bid and Antiapoptotic Bcl-2 Homologues

Abstract: As a model for defining the role of lysosomal cathepsins in apoptosis, we characterized the action of the lysosomotropic agent LeuLeuOMe using distinct cellular models. LeuLeuOMe induces lysosomal membrane permeabilization, resulting in release of lysosomal cathepsins that cleave the proapoptotic Bcl-2 family member Bid and degrade the antiapoptotic member Bcl-2, Bcl-xL, or Mcl-1. The papain-like cysteine protease inhibitor E-64d largely prevented apoptosis, Bid cleavage, and Bcl-2/Bcl-xL/Mcl-1 degradation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
262
4
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(282 citation statements)
references
References 65 publications
(82 reference statements)
10
262
4
2
Order By: Relevance
“…If extensive, the oxidative process might propagate to the lysosomal membrane, where lipid peroxidation results in LMP and release of lysosomal contents, namely acidic hydrolases and low mass redox-active iron, into the cytoplasm. 48 Simultaneous staining by DCF and LysoTracker Red indicates that many, but not all lysosomes undergo a burst of oxidative reactions, which likely account for LMP. Importantly, this finding shows that lysosomes are differently sensitive to oxidation, probably because of different contents or redox-active iron.…”
Section: Discussionmentioning
confidence: 99%
“…If extensive, the oxidative process might propagate to the lysosomal membrane, where lipid peroxidation results in LMP and release of lysosomal contents, namely acidic hydrolases and low mass redox-active iron, into the cytoplasm. 48 Simultaneous staining by DCF and LysoTracker Red indicates that many, but not all lysosomes undergo a burst of oxidative reactions, which likely account for LMP. Importantly, this finding shows that lysosomes are differently sensitive to oxidation, probably because of different contents or redox-active iron.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal cathepsins can be categorized as cysteine (cathepsins B, C, F, H, K, L, O, S, V, W and X), aspartic (cathepsins D and E) and serine (cathepsin G) proteases (Eskelinen and Saftig, 2008, Kuester et al, 2008, Turk et al, 2002. They have a pH optimum of around 5, although several of them remain active even at neutral pH from minutes (cathepsin L) to hours (cathepsin S) (Droga-Mazovec et al, 2008).…”
Section: The Role Of Lysosomes In Intracellular Iron Metabolismmentioning
confidence: 99%
“…Apoptosis occurs via a mitochondrial-dependent intrinsic pathway or a death receptor-mediated extrinsic pathway [23][24][25] . The intrinsic pathway of apoptosis is regulated by members of the Bcl-2 family, which is composed of proapoptotic members (ie, Bax, and Bad) and anti-apoptotic members (ie, Bcl-2 and Bcl-X L ).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin-induced apoptosis is mediated via caspase activation in NTera-2 cells Caspases are cell-death proteases that play a significant role in both the initiation and execution of apoptotic programs in diverse species [20,21] . Caspase assays revealed that curcumin induced caspase 9, 8, and 3 activation in a dose-dependent manner, and the levels of cleaved PARP also increased ( Figure 3B).…”
Section: Curcumin Treatment Inhibited the Proliferation Of Testicularmentioning
confidence: 99%
See 1 more Smart Citation